Awareness on Elementary Schools English Handbook: Teaching Material Appropriateness Survey Research - Yuyun Hendrety; Farnia Sari; Amalia Hasanah; Yunani Atmanegara (Ta'dib: Jurnal Pendidikan Islam, 2022)
This study aims to investigate teachers’ and students’ awareness on elementary schools students’ English handbook in terms of the students’ need and interest. It was a survey research involving 5 teachers of English and also 120 fifth grade students at Madrasah Ibtidaiyah Negeri II Palembang. A likert scale questionnaire was distributed as the instrument which was validated and tried out to determine the rigor of the instrument. The data was analyzed by using descriptive analysis. The finding revealed that dealing with elementary schools students English handbook, the teachers tended to disagree that that it was designed based on childrens’ need and interest at the aspect of teaching material, but they agreed that the English handbook fulfilled students’ need and interest in terms of teaching and learning process. Then, students tended to agree that their English handbook fulfil their need and interest. Teachers tended to agree that they need to do some adaptation when using the handbook. Dealing with expectation, teachers tended to strongly disagree that there should be both evaluation and improvement given by the government related to the use of the elementary schools students’ English handbook. In contrast, children tended to agree that government should evaluate and improve the use of elementary schools students English handbook.